In Another Time - Schindler, Harold (University Press of Colorado, 1998)
An illustrated collection of historical articles originally published in the Salt Lake Tribune from 1993 to 1996, In Another Time provides both an entertaining introduction to Utah and a distinguished and popular historian's summary views of the state's peculiar history. Another Time will entertain and inform newcomers seeking an introductory understanding of what has made Utah different, old hands wanting to know more about the rich complexity of the state's past, and anyone who enjoys well-told historical tales.